THE TRADITION OF KHAMSA AND THE PLACE OF THE DASTAN "GULSHAN UL-ANVAR" BY YAHYA BEY TASHLICALI (Scientific journal of the Fergana State University, 2025)
This article analyzes the development of the Khamsa tradition in Eastern literature, focusing on the examples of the first epics in Nizami Ganjavi’s and Tashlijali Yahya Bey’s "Khamsa" collections. Tashlijali Yahya Bey, a prominent figure in Ottoman Turkish literature, is shown to have modeled the structure of his first epic "Gulshan ul-anvar" after Ganjavi’s "Makhzan ul-asror" and Navoi’s "Hayrat ul-abror." This is demonstrated through specific examples. In particular, the article highlights a significant innovation in the epic - the crucial role of three basmala chapters in the composition of the poem. The analysis of the structure and essence of these chapters, which do not exist as separate chapters in Nizami’s epic, serves to substantiate the author's artistic mastery and individual style.